Consultation Forms for Walk-In Clientele and Landscape Site Visits - Amanda D. Ali; Laura A. Warner; Sydney Park Brown; Susan Haddock; Laurie Albrecht (EDIS)
This 8-page fact sheet contains forms for horticulture Extension agents and staff to use during walk-in consultations and/or on-site consultations related to plant identification, problem diagnosis, and cultural advice. The forms are available as fillable PDFs. Written by Amanda D. Ali, Laura A. Warner, Sydney Park Brown, Susan Haddock, and Laurie Albrecht and published by the Department of Agricultural Education and Communication, March 2017.